Layer-by-layer assembly of nitrogen-doped graphene quantum dots monolayer decorated one-dimensional semiconductor nanoarchitectures for solar-driven water splitting. Issue 42 (6th October 2016) - Zeng, Zhiping; Xiao, Fang-Xing; Gui, Xuchun; Wang, Rong; Liu, Bin; Yang Tan, Timothy Thatt
Abstract : A layer-by-layer assembly of highly ordered nitrogen-doped graphene quantum dots (N-GQDs)/ZnO nanowire (NW) heterostructures was demonstrated as a high performance photoanode in photoelectrochemical hydrogen generation. Abstract : A layer-by-layer (LbL) assembly of highly ordered nitrogen-doped graphene quantum dots (N-GQDs)/ZnO nanowire (NW) heterostructures was demonstrated as a high performance photoanode in photoelectrochemical (PEC) hydrogen generation for the first time. The nitrogen doping of GQDs was achieved by a facile synthesis strategy under ambient conditions, based on which N-GQDs were uniformly and intimately deposited on the ZnO NW framework via pronounced electrostatic interaction. The deposited amount of N-GQDs and PEC water splitting performances of N-GQDs/one-dimensional (1D) semiconductor heterostructures can be tuned by the assembly layer. The integrative roles of nitrogen doping and photosensitization of GQDs in conjunction with intimate interfacial integration between the photoanode components afforded by the LbL assembly strategy were found to collaboratively contribute to enhanced PEC water splitting. It is anticipated that our work could afford a facile and general strategy for steering toward the rational design of a large variety of N-GQDs/1D semiconductor nanoarchitectures for extensive photocatalytic or PEC applications.